2018
DOI: 10.1177/1461348417747180
|View full text |Cite
|
Sign up to set email alerts
|

The wavelet transfer function of a human body–seat system

Abstract: In the analysis of vibration systems, classical transfer functions are used. Usually, it is the ratio of Fourier or Laplace transforms. The wavelet transfer function is proposed in this work. In this paper, the wavelets transfer function is the ratio of output and input wavelet transforms. It is considered as a distinctive correlation of the output and input system signals. The wavelet transform consists of coefficients, where the first is a scale and second time shift. To get input and output signals in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The passive suspension system was investigated by using wavelet transfer function (WTF) in work. 6 The WTF calculated in this case showed that the examined seat suspension system may amplify vibrations in the widerfrequency range, exceeding resonance range for the same periods in time signal history. The essential feature, and in the same way, lack of passive systems, is observed when WTF is calculated for the driver's head.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…The passive suspension system was investigated by using wavelet transfer function (WTF) in work. 6 The WTF calculated in this case showed that the examined seat suspension system may amplify vibrations in the widerfrequency range, exceeding resonance range for the same periods in time signal history. The essential feature, and in the same way, lack of passive systems, is observed when WTF is calculated for the driver's head.…”
Section: Introductionmentioning
confidence: 71%
“…The methodology and experiment procedure are introduced and presented in detail in Blazejewski et al, 6 where the passive seat suspension is considered. In this work, the same methodology and procedure are applied in the case of active suspension in order to compare both systems.…”
Section: Vibration Experiments Measurements and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the Fourier transforms, which localize the frequency, but do not give a temporal resolution of the process, and from the apparatus of delta functions, which localizes time instants, but does not have a frequency resolution, a WT that has a self-adjusting movable time-frequency window identifies both lowfrequency and high-frequency characteristics of the signal at different time intervals. The indicated universality of wavelet analysis leads to its widespread use in various fields of knowledge [6], [7]. Discrete WT is widely used in engineering and programming, and continuous WT -in scientific research.…”
Section: Introductionmentioning
confidence: 99%